Microstructured Waveguide Sensors for Point-of-Care Health Screening - Svetlana S. Konnova; Pavel A. Lepilin; Anastasia A. Zanishevskaya; Alexey Y. Gryaznov; Natalia A. Kosheleva; Victoria P. Ilinskaya; Julia S. Skibina; Valery V. Tuchin (Photonics)
Biosensor technologies in medicine, as in many other areas, are replacing labor-intensive methods of monitoring human health. This paper presents the results of experimental studies on label-free sensors based on a hollow core microstructured optical waveguide (HC-MOW) for human blood serum analysis. The MOWs with a hollow core of 247.5 µm in diameter were manufactured and used in our work. These parameters allow the hollow core to be filled with high-viscosity solutions due to the capillary properties of the fiber. Calculations of the spectral properties of the HC-MOW fiber were carried out and experimentally confirmed. Twenty-one blood serum samples from volunteers were analyzed using standard photometry (commercial kits) and an experimental biosensor. The obtained transmission spectra were processed by the principal component analysis method and conclusions were drawn about the possibility of using this biosensor in point-of-care medicine. A significant difference was shown between the blood serum of healthy patients and patients with confirmed diagnoses and a long history of cardiovascular system abnormalities. Algorithms for spectra processing using the Origin program are presented.